P527 Body image dissatisfaction is increased in inflammatory bowel disease compared with healthy matched controls but not diseased controls. (25th January 2019) - Su, H; Chen, A; Brown, S; Alcantara, J; Sim, D; Myint, H; Lilic, P; Inns, S
Abstract: Background: Body image dissatisfaction (BID) is increased in inflammatory bowel disease (IBD) and also in other chronic medical conditions. Whether the high rate of BID in IBD is a function of chronic disease in general or a particular feature of IBD is unknown. We aimed to compare BID in IBD to age- and gender-matched healthy and chronic disease control groups. We chose Type 1 diabetes as the control disease because of its demographic similarities to IBD but relative lack of known risk factors for BID. Methods: A case–control study was conducted in Hutt Valley Hospital. Consecutive cases, aged 16 years and over, were matched 1:1:1 to normal and diabetes controls for age and gender. Cases with recent surgery, pregnancy, or other significant chronic medical diagnoses were excluded. Participant demographics were collected. Participants were asked to complete the Body Image Disturbance Questionnaire (BIDQ), the hospital anxiety and depression score (HADS), and Quality of Life measures (RAND 36). Results: There were 45 age- and gender-matched pairs for comparison of IBD and healthy controls, and 38 for IBD and diabetic controls. 77% of the participants were female. The mean BIDQ was higher in IBD patients compared with controls (2.05 vs. 1.58, p = 0.001) but not when compared with diabetics (2.03 vs. 1.72, p = 0.77). There was no difference in mean BMI, smoking status, or relationship status between groups. IBD patients scored more highly than controls for depression (mean HDS 6.51 vs. 3.87, p = 0.002) but not for anxiety (mean HAS 5.51 vs. 4.89, p = 0.258). No difference was seen between IBD and diabetic in either HADS domain. In IBD cases, logistic regression showed increased risk of depression (OR 4.6, p = 0.025) and anxiety (OR 7.4, p = 0.015) for every 1 point increase in BIDQ, after adjusting for clinical remission, gender, age, BMI, and smoking status. Conclusions: Our data suggest that while BID is increased in IBD patients, it may not relate directly to the effects of IBD itself, but rather is a feature of chronic disease. Increased BID is associated with the presence of depression and anxiety in IBD patients. There may be a role for diagnosing and treating BID in IBD patients.